Vegetative growth of raspberry (Rubus idaeus L.) ‘Autumn Bliss’ with vermicompost application intercropped with lupine (Lupinus mutabilis Sweet.) - Jara-Peña, Enoc (2003)
The present investigation was carried out with objective to determine the response of red raspberry to vermicompost application and lupine (intercropped or not) in the phase of vegetative growth under greenhouse conditions in Montecillo, Mexico. In the experiment 11 treatments were studied with 9 replications per treatment, with a complete factorial (5 × 2) plus an additional treatment consisting of a chemical fertilization with N100 P80 K80. As vegetable material adventitious buds of raspberry were used, statistically significant differences were found between treatments in number of leaves, plant height, cane diameter, fresh and dry matter in raspberry. The biggest response was obtained with 90 and 120 g pot–1 of vermicompost. In general, the lupine intercropped with raspberry permitted a slight competion but favored the biggest development in the foliar area.